2020
DOI: 10.1002/smll.202005165
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐Based Metal–Organic Frameworks and Their Potential Applications

Abstract: Metal-organic frameworks (MOFs) built on calcium metal (Ca-MOFs) represent a unique subclass of MOFs featuring high stability, low toxicity, and relatively low density. Ca-MOFs show considerable potential for molecular separations, electronic, magnetic, and biomedical applications, although they are not investigated as extensively as transition metal-based MOFs. Compared to MOFs made of other groups of metals, Ca-MOFs may be particularly advantageous for certain applications such as adsorption and storage of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 241 publications
1
30
0
Order By: Relevance
“…While the vast majority of these materials is constructed using transition metal or rare earth cations, recent efforts have been devoted to the use of s-block ions 4-8 with a particular emphasis on alkaline earth metals such as Ca(II). [9][10] Indeed, it is an inexpensive naturally abundant element, has a lower toxicity and features low density, particularly favourable for gas sorption. These interesting characteristics of Ca-based MOFs come with a catch, since the coordination number and geometry of this cation are harder to predict and its oxophilicity makes it prone to coordination by water molecules at the expense of ligand binding, potentially leading to architectures of low dimensionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the vast majority of these materials is constructed using transition metal or rare earth cations, recent efforts have been devoted to the use of s-block ions 4-8 with a particular emphasis on alkaline earth metals such as Ca(II). [9][10] Indeed, it is an inexpensive naturally abundant element, has a lower toxicity and features low density, particularly favourable for gas sorption. These interesting characteristics of Ca-based MOFs come with a catch, since the coordination number and geometry of this cation are harder to predict and its oxophilicity makes it prone to coordination by water molecules at the expense of ligand binding, potentially leading to architectures of low dimensionality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the solvothermal approach is the preferred synthetic method over the hydrothermal one, to prevent competing coordination by water, although synthesis based on water/solvent combinations have been reported. [7][8][9][10] Surprisingly, to the best of our knowledge and according to a recent review, 10 there have been no reports of Ca-MOFs prepared following the ionothermal strategy, in spite of its appealing characteristics for such purposes. [11][12][13][14][15] This methodology is based on the use of an ionic environment to act as solvent and template for the formation of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…As a new class of porous materials, porous metal-organic frameworks (PMOFs) build from organic ligands and metal ions or polynuclear clusters via coordination bonds have been widely used in the fields of gas storage and separation, heterogeneous catalysis, luminescence sensing, and so on, owing to their adjustable pore geometries and ultra-high porosity. [1][2][3][4][5] Among these applications of PMOFs, the function of PMOFs with luminescence detection for diverse targets, including metal ions, anions, volatile organic compounds, small molecules, nitroaromatic explosives, gases, and biomolecules, have attracted extensive attention. [6][7][8][9][10] Compared with the traditional detection techniques, the advantages of luminescence sensing method with PMOFs are the high selectivity and sensitivity, quick response, low cost, and even observable color change by naked eyes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the latest review by Xian et al (2021), more than 150 Ca-CPs have been reported so far. Mantion et al (2008) reported the first 'bio-inspired' MOFs constructed from an oligovaline peptide and calcium(II).…”
Section: Introductionmentioning
confidence: 99%